Unlocking the Paradox: Exploring the Impact of Management Paradox Thinking on Corporate Innovation Performance - Binbin Zhao; Zhongli Zhang; Mengyun Zhang (SAGE Open)
Paradoxical thinking (PT), a cognitive approach to addressing conflicting managerial demands, plays a dual role in shaping corporate innovation outcomes. This study explores how PT in team management affects innovation performance using a dual-path model based on data from 122 enterprise innovation teams. The findings show that while PT enhances innovation by fostering employee action learning (AL), it also impairs performance by increasing Cognitive load (CL). Additionally, power distance strengthens the positive mediating effect of AL but does not significantly influence the negative impact of CL. These findings contribute to organizational behavior research by deepening the understanding of cognitive strategies and offering practical insights for managing cognitive demands in team-based innovation.